The Role of Notaries in Making Agreements for the Sharing of Joint Assets for Supplies who will Divorce without a Marriage Agreement - Desi Arisandi; Andri Winjaya L; Dini Amalia Fitri (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
Property as a life support for the bride and groom in the marriage bond. Where the property is obtained before the marriage (innate property) and obtained during the marriage (joint property). If the marriage bond is dissolved or broken, then each of them will defend their rights to the joint property so that the joint property is often a serious problem and often creates debate between the two parties (husband and wife).The research approach method used in this thesis is sociological juridical. This research specification uses descriptive analysis. The type of data used in this research is primary data which includes the 1945 Constitution; Act No. 2 of 2014 concerning the Position of a Notary; Act No. 16 of 2019 on the amendment to Act No. 1 of 1974 concerning Marriage; Code of Civil law; Compilation of Islamic Law, as well as secondary data containing books and other supporting documents. Collecting research data with interview techniques and study of documents or library materials. The data analysis method used is qualitative analysis.The results of the research and discussion that: First; the division of joint property for couples who are going to divorce in the concept of justice, namely dividing joint property equally or equally. This is in line with what has been regulated in the Marriage Law, the Civil Code and the compilation of Islamic Law which states that if there is a divorce, the joint assets are divided equally. Second; The role of a notary in making a deed of a joint property distribution agreement for a divorced couple without a marriage agreement, namely a notary as a public official who has the authority to make an authentic deed including a deed of a joint property distribution agreement based on the will of both parties who agree to share their assets in accordance with the law. applicable.